Synthesis of ω‐Muricholic Acid by One‐Pot Enzymatic Mitsunobu Inversion using Hydroxysteroid Dehydrogenases. Issue 23 (22nd October 2021) - Bertuletti, Susanna; Ferrandi, Erica Elisa; Monti, Daniela; Fronza, Giovanni; Bassanini, Ivan; Riva, Sergio
Abstract: The biocatalyzed conversion of hyocholic acid (3α, 6α, 7α‐trihydroxy‐5β‐cholan‐24‐oic acid) into ω‐muricholic acid (3α, 6α, 7β‐trihydroxy‐5β‐cholan‐24‐oic acid) has been obtained exploiting a small library of 7α‐ and 7β‐HSDHs (hydroxysteroid dehydrogenases). The process has been optimized and performed avoiding the isolation of the 7‐oxo intermediate using the appropriate coupled enzymes for the in situ cofactor regeneration. Moreover, the biocatalyzed reduction of 6, 7‐dioxolithocholic acid (3α‐hydroxy‐6, 7‐dioxo‐5β‐cholan‐24‐oic acid) was also investigated. Abstract : One‐pot reaction : ω‐Muricholic acid was obtained from its 7α‐epimer hyocholic acid via 7α‐ and 7β‐HSDH‐mediated one‐pot redox biotransformations.